COMPONENTS OF THE BANK’S POTENTIAL AND THEIR DEVELOPMENT THROUGH INNOVATIVE ACTIVITY IN THE FIELD OF DIGITAL ECONOMY - PROSOVYCH, Olha; CHUCHMAN, Ihor-Bohdan; GRYBYK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The relevance of the study is due to the transformation of the banking sector under the influence of digitalization, which changes the structure of banks’ potential and puts forward new requirements for their innovative activity. The article examines the key components of banking potential and shows their evolution in the digital economy. The purpose of the article is a comprehensive study of the components of the bank’s potential and substantiation of the mechanisms of their development through innovative activity in the digital economy. The methodological basis is a systems approach, structural and functional analysis, methods of generalization and induction, as well as statistical analysis of official data of the National Bank of Ukraine. The article identifies and characterizes the components of the banking potential (financial, material and technical, information, personnel, organizational, credit and investment, innovative, market). The transformation of the material and technical base is analyzed due to the reduction of branches and the growth of the role of digital service channels. The role of innovative activity as a factor in the development of all components of the potential (from online lending to the implementation of big data, AI, blockchain, BNPL) is proven. A comparison of traditional banks and neobanks was conducted, which made it possible to show a fundamental difference in the organization of business models: digital banks (such as monobank) achieve higher efficiency due to the complete absence of a physical network, faster time-to-market and orientation towards digital services. Risks were identified - increased dependence on IT infrastructure and cyber threats, which requires the development of protective mechanisms. The practical significance of the results lies in the possibility of their use by heads of banking institutions for strategic planning, development of digital transformation policies and management of personnel and technological development. In addition, the results of the study will be useful for scientists and students of economic specialties as a theoretical and methodological basis for further research in the field of digital finance.